Imaging of Community-acquired Pneumonia - Franquet, Tomás (Journal of thoracic imaging, 2018)
Community-acquired pneumonia refers to an acute infection of the lung in patients who did not meet any of the criteria for health care-acquired pneumonia, and is associated with at least some symptoms of acute infection, accompanied by the presence of an acute infiltrate on a chest radiograph. Chest radiography remains an important component of the evaluation of a patient with a suspicion of pneumonia, and is usually the first examination to be obtained. The diagnosis of community-acquired pneumonia is based on the presence of select clinical features and is supported by imaging of the lung, usually by chest radiography. Infection of the lower respiratory tract typically presents radiologically as one of 3 patterns: (a) focal nonsegmental or lobar pneumonia, (b) multifocal bronchopneumonia or lobular pneumonia, and (c) focal or diffuse "interstitial" pneumonia. High-resolution computed tomography allows a better depiction of the pattern and distribution of pneumonia than the radiograph but is seldom required in the evaluation of patients with suspected or proven bacterial pneumonia. However, high-resolution computed tomography is a useful adjunct to conventional radiography in selected cases.